Parametric Assessment of Surface Topography and Its Influence on Joint Tightness of Non-Separable Joints for Thin Wall Applications - Nikodem Wróbel; Michał Rejek; Jolanta Królczyk; Mateusz Franka; Munish Kumar Gupta; Marcin Śliwiński; Grzegorz Królczyk (Applied Sciences, 2022)
This article describes the research carried out on six thin-walled groups of samples produced from the aluminum alloy 6060 T4 by a turning and milling operation. Additionally, the analysis of the surface topography was carried out, focusing on three-dimensional parameters, such as Sq, Ssk, Sku, Sp, Sv, Sz, Sa, Spd, and Spc. Moreover, the article contains the tests of the tightness of various types of surfaces with different clamping forces of the tested elements. Furthermore, an attempt was made to find significant representatives of the surface topography to obtain the smallest leakage between the mating surfaces. The maximum clamping force obtained in the tests between the pairs was 9060 N. Finally, it is worth mentioning that the presented surface tests can serve as the required parameters for joined elements in the production of non-detachable joints by, for example, clinching.